Leprosy in posteradication era – A clinicopathological correlation: How far we have achieved? - Deepti Gangwar; Amitosh Mishra; Sara Siddiqui; Sangeeta Bohara; Bushra Khanam (Asian Journal of Medical Sciences, 2022)
Background: Leprosy or “Hansen Disease” is chronic inflammatory disease caused by Mycobacterium leprae. This disease is the oldest disease known to mankind. Leprosy is also known as “Kushtaroga.”. Leprosy was considered as an eradicated disease in 2005 but still a large number of leprosy cases are being reported in India. Aims and Objectives: The aim of the study was to demonstrate that leprosy even being eradicated continuous to be a major health concern with changing trends. Materials and Methods: This study is a a hospital-based crossectional study; it involves all new patients of leprosy attending dermatology O.P.D HIMS, Safedabad, Barabanki, U.P. from 2015 to 2016. The cases were classified as per Ridley – jopling classification. Skin biopsies were taken from all clinically suspected cases of leprosy and these biopsies were studied using H&E stain. Results: In our study, 53 leprosy cases were registered from April 2015 to April 2016. According to demographic details of leprosy cases, maximum number of cases were in the age group 31–40 years 38.9% and in individuals <20 years 10.5%. Majority of cases were males (11.3%). The family history of leprosy was present in 9.4% of patients. Hypopigmented lesion on skin was most common symptom (32.1%). TT was most common clinical diagnosis (26.4%). IL was common histopathological diagnosis (26.4%). Atrophy of epidermis was seen in 50.9% of patients. Paucibacillary was seen in 62.3% of patients. Most of the cases were from Safedabad. Conclusion: Leprosy although reported to be eradicated still continues to be one of the common communicable disease in Uttar Pradesh, India. This necessitates to strengthen screening of cases, early detection, and revival of our knowledge regarding the disease.